PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL FETISH JARIK - Pratiwi, Hanny Dila Intan; Setyorini, Erny Herlin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This research aims to find answers to legal protection efforts obtained by victims of finger fetish abuse. Which will be reviewed from the legal protection of children and adults who are victims. By paying attention to the decision of the case and the positive law that was in effect at the time the case was being handled or at the time this case occurred. Contains the legal rules and laws that are used when the judge decides on this finger fetish case. This research will later be reviewed from the Law on Child Protection and the Law on the Protection of Witnesses and Victims as well as the Criminal Code and other legal regulations related to the legal issues raised. Researchers use the type of normative juridical legal research and use a conceptual approach, statute approach, and case approach. By reviewing and analyzing the legal protection that victims receive, they will be able to solve legal problems regarding the legal issues being researched. So that later in order to obtain answers from the results of the study of the journals that have been researched